Influence of Precision Nutrient Management on Dry Matter Accumulation and Partitioning of Rice in Southern Odisha - Sagar, Lalichetti; Maitra, Sagar; Singh, Sultan; Sairam, Masina (Agricultural science digest, 2023)
Background: The nutrient management practices are largely known to influence dry matter accumulation and translocation in rice. However, the role of precision nutrient management in dry matter partitioning to the reproductive parts of rice is still unexplored. Methods: The present trial was conducted during boro season of 2021-22 at PG Experimental Farm, MSSSoA, CUTM, Odisha. The experiment was laid out in randomized block design with 11treatments that were replicated thrice. The treatments examined under the investigation were namely, absolute control, 75% recommended dose of fertilizer (RDF), 100% RDF, 125% RDF, 75% RDF fb nano urea spray @ 2ml/L at panicle initiation, 100% RDF fb nano urea spray @ 2ml/L at panicle initiation, leaf colour chart (LCC) 3 basednitrogen management, LCC 4 based nitrogen management, sufficiency Index (SI)-based N management at a threshold value less than 90%, Nutrient expert (NE) based nutrient recommendation, Rice crop manager (RCM) based nutrient recommendation. Result: The results of the study indicated that SI-based N management at a threshold value less than 90% results in highest allocation, shoot dry matter to the panicle (53.46%); while, absolute control of nutrients resulted in highest percentage allocation of shoot dry matter to culm (23.72%) and leaves (33.88%) during maturity.